Capacitor coupled converter (C3) for high power DC conversion - Ehsani, Morteza; Bilgiç, Mehmet Oruç; Khan, S.; Laskai, L.; Jeong, Seung-Gi (IEEE, 1995)
The bang-bang controlled capacitor coupled converter (C3) is described in this paper. Due to the converter's inherent commutating property, the C3 can accommodate thyristors as well as high-power gate turn-off switches, due to zero-current switching transitions. The zero-current switching is achieved at no current stress increase, therefore, the topology is considered appropriate for high-power processing. DC and small signal AC models are derived for the bang-bang controlled C3, a design procedure is proposed, and simulation results are discussed. Finally, oscillograms from a proof of principle prototype circuit are presented
Keywords: Power Electronics; Converter